2009
DOI: 10.1080/10509670903081359
|View full text |Cite
|
Sign up to set email alerts
|

Offenders' Perceptions of House Arrest and Electronic Monitoring

Abstract: This article reports on a study designed to examine the perceptions of house arrest (HA) and electronic monitoring (EM) among offenders who have recently experienced this criminal sentence. Data were gathered via a self-administered questionnaire and follow-up interviews with a sample of offenders. Our primary areas of interest were to assess (a) the extent to which HA and EM are perceived as punitive, (b) the extent to which this sanction impacts the offenders at home and at work, and (c) to explore the ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 19 publications
3
23
0
4
Order By: Relevance
“…Empirical evidence that distinguishes between these two mechanisms is rare. But even though qualitative studies have found that wearing a visible GPS tracker produces public shame (e.g., Martin, Hanrahan, & Bowers, ), existing studies argue that other people are likely to view imprisonment as more stigmatizing (e.g., Western, Kling, & Weiman, ). Also, serving a prison sentence at home under electronic monitoring reduces the offender's absence from society, making it easier for the offender to keep or at least search for a job or a partner.…”
Section: Partnership Incarceration and Divorcementioning
confidence: 99%
“…Empirical evidence that distinguishes between these two mechanisms is rare. But even though qualitative studies have found that wearing a visible GPS tracker produces public shame (e.g., Martin, Hanrahan, & Bowers, ), existing studies argue that other people are likely to view imprisonment as more stigmatizing (e.g., Western, Kling, & Weiman, ). Also, serving a prison sentence at home under electronic monitoring reduces the offender's absence from society, making it easier for the offender to keep or at least search for a job or a partner.…”
Section: Partnership Incarceration and Divorcementioning
confidence: 99%
“…Des 188 lettres qui ne nous ont pas été retournées, 47 répondants ont indiqué vouloir participer à l'étude. C'est un taux de participation que l'on peut considérer comme relativement haut, car dans une étude antérieure impliquant des sursitaires, 141 lettres avaient été envoyées, mais seulement 12 personnes avaient participé à l'étude (Martin, Hanrahan et Bowers Jr, 2009). Les répondants de notre étude provenaient de la ville de Québec et des régions avoisinantes (Beauce, Chaudière-Appalaches, Mauricie et Centre-du-Québec).…”
Section: Méthodeunclassified
“…Ces conditions peuvent, notamment, obliger le sursitaire à se soumettre à un traitement psychosocial ou encore à demeurer à son domicile à des heures prescrites (couvre-feu et assignation à domicile). Très peu d'études ont porté sur le sursis (F. -Dufour, Brassard et Guay, 2009 ;Lehalle, Landreville et Charest, 2009 ;Martin, Hanrahan et Bowers, 2009 ;Padgett, Bales et Blomberg, 2006 ;Stanz et Tewksbury, 2000). Le peu d'études disponibles, souvent produites sous forme d'enquêtes statistiques, montre néanmoins que cette peine est efficace selon l'indice de mesure de la récidive (voir F.-Dufour et al, 2009).…”
Section: Revue De La Littératureunclassified
“…Des 188 répondants potentiels qui semblent avoir reçu la lettre, 47 ont indiqué vouloir participer à l'étude. C'est un taux de participation que l'on peut considérer relativement haut, car dans une étude impliquant des sursitaires, 141 lettres avaient été envoyées, mais seulement 12 personnes y avaient participé (Martin et al, 2009). Au total, 29 répondants ont été interviewés.…”
Section: Méthodologieunclassified
See 1 more Smart Citation